2013
DOI: 10.5646/jksh.2013.19.3.71
|View full text |Cite
|
Sign up to set email alerts
|

Association of Inter-arm Blood Pressure Difference with Atherosclerosis in Patients without Cardiovascular Diseases

Abstract: Blood pressure (BP) measurement is the most common investigation performed in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 26 publications
1
12
2
Order By: Relevance
“…Inaddition, sIAD levels have been found to be associated with a significantly increased risk of future cardiovascular events [18]. The prevalence of of high sIAD (23.4%) in our result is higher than those reported by Su and colleagues [19] and Kim and colleagues [20], and is lower than that reported by Clark and colleagues [21], but is similar to that reported by Tak and colleagues [22]. In addition, it was similar to the result of a meta-analysis performed by Clack and colleagues [23].…”
Section: V Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Inaddition, sIAD levels have been found to be associated with a significantly increased risk of future cardiovascular events [18]. The prevalence of of high sIAD (23.4%) in our result is higher than those reported by Su and colleagues [19] and Kim and colleagues [20], and is lower than that reported by Clark and colleagues [21], but is similar to that reported by Tak and colleagues [22]. In addition, it was similar to the result of a meta-analysis performed by Clack and colleagues [23].…”
Section: V Discussioncontrasting
confidence: 57%
“…Kim and colleagues reported that obesity status (men, p=0.757; women, p=0.185) was not significantly related to sIAD levels [22]. However, in their study, the mean sIAD level (men, 3.19±2.38 mmHg; women, 2.61±2.18 mmHg) and the prevalence of high sIAD (men, 1.9%; women, 0%) were lower than those in our study.…”
Section: V Discussioncontrasting
confidence: 55%
“…Our results revealed that the right arm BP was higher than the left arm BP, which was in consistent with results of previous studies. 4) 14) 27) A possible explanation is that muscles in the dominant arm are more developed that it might take more pressure in the right arm cuff to overcome tissue inertia. Hence, BP in the right arm of right handed people might be measured higher than the BP in their left arm.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, BP in the right arm of right handed people might be measured higher than the BP in their left arm. 4) In addition, slight differences of anatomical structures such as angulation and branching of the aorta as well as hemodynamic profiles might have affected the result. 28)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation